Serial measurement of B-type natriuretic peptide and future cardiovascular events in patients with type 2 diabetes mellitus without known cardiovascular disease. (1st June 2022) - Ikeda, Shota; Shinohara, Keisuke; Enzan, Nobuyuki; Matsushima, Shouji; Tohyama, Takeshi; Funakoshi, Kouta; Kishimoto, Junji; Itoh, Hiroshi; Komuro, Issei; Tsutsui, Hiroyuki
Abstract: Background: In patients with type 2 diabetes mellitus (T2DM) without known cardiovascular disease, the association between B-type natriuretic peptide (BNP) and cardiovascular events except for heart failure has not been elucidated. We aimed to investigate this association in high-risk T2DM patients. Methods: We analyzed the association between BNP and cardiovascular events, including coronary, cerebral, renal, and vascular events or cardiovascular death based on the single and serial measurement of BNP in T2DM patients with retinopathy and hyperlipidemia without known cardiovascular disease enrolled in the EMPATHY study. Results: Data from 4966 patients were analyzed for baseline BNP analysis. The median BN P value was 15.0 pg/mL. When analyzed in quartiles of baseline BNP (interquartile range 7.5–29.2 pg/mL), Q2, Q3, and Q4 were associated with cardiovascular events compared with Q1 (hazard ratio [HR]: Q2, 1.91 [ P = 0.003]; Q3, 1.63 [ P = 0.031]; Q4, 3.20 [ P < 0.001]). The analysis of 12-month BNP showed similar associations. In serial BNP measurement, compared with low–low BNP group (baseline ≤35 pg/mL and 12-month ≤35 pg/mL), low–high BNP group as well as high–high BNP group was associated with cardiovascular events (HR: low–high, 2.05 [ P = 0.004]; high–high, 2.07 [ P = 0.001]) and non-renal cardiovascular events. High–low BNP group tended to be associated with non-renal cardiovascular events (HR vs low–low: 2.05 [ P = 0.056]). Conclusions: BNP levels were associated with first cardiovascular events except for heart failure in T2DM patients with retinopathy and hyperlipidemia. Serial BNP measurement may be useful in further stratifying high-risk patients among this T2DM population. Graphical abstract: Unlabelled Image Highlights: We analyzed the association between BNP and CV events in T2DM patients enrolled in the EMPATHY study. BNP levels were associated with non-heart failure CV events in T2DM with retinopathy and hyperlipidemia without known CVD. Serial BNP measurement may be useful in further stratifying high-risk patients among this T2DM population.